Application Of Importance Performance Analysis Method In Measuring Satisfaction Level Students On Learning In School - David Tri Julian; Herlina Latipa Sari; Jhoanne Fredricka (Jurnal Media Computer Science, 2022)
Pelita Kasih High School which is a private school located in Bengkulu City. So far, the learning process at Pelita Kasih High School often makes students feel bored and lack understanding and mastery of the material that has been taught. This makes the school, especially the teacher, must conduct an analysis to determine the level of student satisfaction with the learning system every semester. However, the obstacle that occurs is that Pelita Kasih High School does not yet have a forum that can help students to provide assessments related to learning satisfaction in schools that are ongoing per semester. Applications measuring the level of student satisfaction with learning at Pelita Kasih High School Bengkulu are used to assist the school in knowing the level of student satisfaction per semester per academic year based on filling out the questionnaire form that has been done by students. The application to measure the level of student satisfaction has applied the IPA (Importance Performance Analysis) method which is used to determine the level of suitability of respondents based on the level of interest and level of satisfaction that has been given by students. The application to measure the level of student satisfaction with learning at SMA Pelita Kasih Bengkulu was made using the Visual Basic .Net programming language. Based on the assessment of 18 students in the Even Semester of the 2021/2022 Academic Year, the average respondent suitability level (TKi) was 91.57% and showed that the level of student satisfaction with learning at school was very satisfied..